Preventing a Biochemical Arms Race. - Kelle, Alexander (Stanford University Press, 2012)
Preventing a Biochemical Arms Race responds to a growing concern that changes in the life sciences and the nature of warfare could lead to a resurgent interest in chemical and biological weapons (CBW) capabilities. By bringing together a wide range of historical material and current literature in the field of CBW arms control, the book reveals how these two disparate fields might be integrated to precipitate a biochemical arms race among major powers, rogue states, or even non-state actors. It seeks to raise awareness among policy practitioners, the academic community, and the media that such a.